Comparative Genomics of Mycobacterium avium Subspecies Paratuberculosis Sheep Strains - Mizzi, Rachel; Timms, Verlaine J.; Price-Carter, Marian L.; Gautam, Milan; Whittington, Richard; Heuer, Cord; Biggs, Patrick J.; Plain, Karren M. (Frontiers in Veterinary Science, 2021)
Mycobacterium avium subspecies paratuberculosis (MAP) is the aetiological agent of Johne’s disease (JD), a chronic enteritis that causes major losses to the global livestock industry. Further, it has been associated with human Crohn’s disease. Several strains of MAP have been identified, the two major groups being sheep strain MAP, which includes the Type I and Type III sub-lineages, and the cattle strain or Type II MAP lineage, of which bison strains are a sub-grouping. Major genotypic, phenotypic and pathogenic variations have been identified in prior comparisons, but the research has predominately focused on cattle strains of MAP. In countries where the sheep industries are more prevalent, however, such as Australia and New Zealand, ovine JD is a substantial burden. An information gap exists regarding the genomic differences between sheep strain sub-lineages and the relevance of Type I and Type III MAP in terms of epidemiology and/or pathogenicity. We therefore investigated sheep MAP isolates from Australia and New Zealand using whole genome sequencing. For additional context, sheep MAP genome datasets were downloaded from the Sequence Read Archive and GenBank. The final dataset contained 18 Type III and 16 Type I isolates and the K10 cattle strain MAP reference genome. Using a pan-genome approach, an updated global phylogeny for sheep MAP from de novo assemblies was produced. When rooted with the K10 cattle reference strain, two distinct clades representing the lineages were apparent. The Australian and New Zealand isolates formed a distinct sub-clade within the type I lineage, while the European type I isolates formed another less closely related group. Within the type III lineage, isolates appeared more genetically diverse and were from a greater number of continents. Querying of the pan-genome and verification using BLAST analysis revealed lineage-specific variations (n=13) including genes responsible for metabolism and stress responses. The genetic differences identified may represent important epidemiological and virulence traits specific to sheep MAP. This knowledge will potentially contribute to improved vaccine development and control measures for these strains.